Killing and Bloody Sunday, November 1920 - DOLAN, ANNE (Cambridge University Press, 2006)
21 November 1920 began with the killing of fourteen men in their ?ats, boarding houses, and hotel rooms in Dublin. The Irish Republican Army (IRA) alleged that they were British spies. That afternoon British forces retaliated by ?ring on a crowd of supporters at a Gaelic football match in Croke Park, killing twelve and injuring sixty. The day quickly became known as Bloody Sunday. Much has been made of the afternoon?s events. The shootings in Croke Park have acquired legendary status. Concern with the morning?s killing has been largely limited to whether or not the dead men were the spies the IRA said they were. There has been little or no consideration of the men who did the killing. This article is based on largely unused interviews and statements made by the IRA men involved in this and many of the other days that came to constitute the guerrilla war fought against the British forces in Ireland from January 1919 until July 1921. This morning?s killings are a chilling example of much of what passed for combat during this struggle. Bloody Sunday morning is used here as a means to explore how generally young and untrained IRA men killed and how this type of killing a?ected their lives.
PUBLISHED
Keywords: History; Ireland; Bloody Sunday 1920